Mass Cytometry and Single-Cell Transcriptome Analyses Reveal the Immune Cell Characteristics of Ulcerative Colitis - Luo, Yongxin; Liu, Shiying; Li, Huibiao; Hou, Jiangtao; Lin, Wenjia; Xu, Zewen; Lu, Tianyu; Li, Yanwu; Peng, Bin; Zhang, Shijing; Han, Xue; Kuang, Zuoliang; et al. (Frontiers in Molecular Biosciences, 2022)
Background: The pathogenesis of ulcerative colitis (UC) is closely related to immunity. The immune characteristic differences between active UC (UCa) and inactive UC (UCin) have not been completely explained. Mass cytometry (CyTOF) and single-cell RNA sequencing (scRNA-seq) were used to analyze the immune cells of UCa, UCin and healthy control (HC) subjects to determine the specific immune characteristics. Methods: The immune cell subsets among UCa, UCin, HC were distinguished using CyTOF analysis. scRNA-seq analysis was used to validate the results of CyTOF. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to understand the roles of differential immune cell subsets. Results: After CyTOF analysis and validation of scRNA-seq analysis, differential immune cell subsets mainly contained TNF+IL-17A++ effector memory (EM) Tregs, CXCR3+CTLA4+ EM Tregs, CXCR3++CCR7+ B cells, HLA-DR+CCR7+ dendritic cells (DCs) and CTLA-4+ natural killer (NK) cells. In comparison to HC, CCR6+TNF+CD161+ EM T cells were highly enriched in UCa and UCin. Besides, UCa was characterized by an increase in CD38+TNF+ EM Tregs, CXCR3+CCR4+ naïve B cells, HLA-DR+CD14+IL21+ macrophages/monocytes, HLA-DR+CCR7+ DCs, AHR+CD14+ cytotoxic NK (cNK) cells and CD8A+IFNG+ cNK cells. Decreases in CD38+CD27+ plasmablasts, CXCR3+CD38+ regulatory NK cells, and CXCR3+CCR7+ tolerant NK cells in UCa were discovered. Conclusions: Novel immune cell subsets which was used to distinguish UCa, UCin and HC were identified. This information might be utilized to distinguish the patients with UCa and UCin.